2021
DOI: 10.2174/1574888x16666210215160402
|View full text |Cite
|
Sign up to set email alerts
|

Dental Pulp from Human Exfoliated Deciduous Teeth-derived Stromal Cells Demonstrated Neuronal Potential: In Vivo and In Vitro Studies

Abstract: Background: Mesenchymal stromal cells (MSC) have the potential for self-renewal and differentiation in different tissues, characteristics that encourage their use in regenerative medicine. Dental tissue MSCs are easy to collect, have the same embryonic origin as neurons and have neuronal markers that allow their use in treating neurodegenerative diseases. Human exfoliated deciduous teeth (SHED)-derived stromal cells are considered immature and present positive expression of pluripotency and neuronal markers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…MAP2 , a member of the microtubule-associated protein family, acts on microtubule stability and regulates microtubules in axons and dendrites [ 30 ]. In previous studies,the neural specific makers NeuN, GFAP and MAP2 expression were always used to evaluate the neural differentiation potential of cells [ 51 , 52 ]. The results of our neural induction experiments demonstrated that the induced PHFSCs and SHFSCs have morphological changes towards a neural –like appearance, and these markers ( MAP2 , NeuN and GFAP ) were highly expressed in the neural induction group, indicating that the two HFSCs successfully differentiated into nerve cells.…”
Section: Discussionmentioning
confidence: 99%
“…MAP2 , a member of the microtubule-associated protein family, acts on microtubule stability and regulates microtubules in axons and dendrites [ 30 ]. In previous studies,the neural specific makers NeuN, GFAP and MAP2 expression were always used to evaluate the neural differentiation potential of cells [ 51 , 52 ]. The results of our neural induction experiments demonstrated that the induced PHFSCs and SHFSCs have morphological changes towards a neural –like appearance, and these markers ( MAP2 , NeuN and GFAP ) were highly expressed in the neural induction group, indicating that the two HFSCs successfully differentiated into nerve cells.…”
Section: Discussionmentioning
confidence: 99%
“…DSC-CM contains a variety of cytokines associated with vascular and nerve tissue regeneration, such as VEGF, BDNF, β-NGF, GDNF and neurotrophin-3 (NT-3)[ 101 , 102 ]. To date, DSC-CM has been reported to have the potential to promote bone regeneration[ 103 ], periodontal regeneration[ 104 ], angiogenesis[ 105 ], pulp regeneration[ 106 ], and nerve protection/regeneration[ 105 , 107 - 109 ] with great possibilities for clinical application.…”
Section: Current Limitations and Perspectivesmentioning
confidence: 99%
“…Since 2003, it has been shown that SHEDs express several different neuro-glial cell markers in the growth medium, such as nestin, glial fibrillary acidic protein (GFAP), neuron-specific enolase (NSE), neurofilament medium-chain (NFM), 2' ,3'cyclic nucleotide-3'-phosphodiesterase (CNPase), βIII-tubulin, glutamic acid decarboxylase (GAD), and neuron-specific nuclear protein (NeuN), indicating the embryonic neural crest origin of SHEDs. After inductive neural culture in neurobasal media containing B27 supplement, epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF), expression levels of neuronal markers including βIII-tubulin, GAD, and NeuN were increased, which meant that SHEDs differentiated into neurons (47)(48)(49). Meanwhile, SHEDs developed multicytoplasmic processes immunoreactive to MAP2 and Tau antibodies (1,50).…”
Section: Neurogenesismentioning
confidence: 99%